Comprehensive Assessment of Specific Patient-Reported Outcome Measures for Hand and Wrist Conditions in Adults: A Scoping Review - S. Iskander; G. Halbesma; M.M. Hoogbergen; D. Young-Afat; I.J. Veldhuizen (JPRAS Open)
Purpose: This scoping review aims to assess the various patient-reported outcome measures (PROMs) specifically developed and validated for patients with hand and wrist conditions. The objective is to provide healthcare professionals with an up-to-date overview of the available PROMs, empowering them to make informed decisions in selecting the most appropriate PROM to support personalized care for their patients. Methods: The review adhered to the PRISMA-ScR 2018 checklist and involved a systematic literature search of MEDLINE, Embase, and Cochrane CENTRAL Registry of Trials. Inclusion and exclusion criteria were established, and 2 independent reviewers screened and selected relevant articles. Data were extracted from full-text articles to identify the conditions of the hand or wrist and the PROMs used for measurement. Results: A total of 22 PROMs for hand and wrist conditions were identified, with the Disabilities of the Arm, Shoulder, and Hand (DASH) being the most frequently employed, followed by the Patient Rated Wrist Evaluation and QuickDASH. The utilization of these PROMs was prominent in articles focusing on traumatic hand and wrist conditions, nerve conditions, and joint/arthrosis problems. Additionally, 67 articles (19.7%) employed more than one hand/wrist-specific PROM, and 8 generic PROMs were used in conjunction with hand/wrist-specific PROMs. Conclusion: This review offers a comprehensive overview of the available PROMs to assist healthcare professionals in selecting the most suitable measure for personalized care. The growing use and development of PROMs in this field highlights their increasing relevance in enhancing patient outcomes. Study design: Scoping Review